2003
DOI: 10.1046/j.1365-2265.2003.01901.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of sublinical brain perfusion abnormalities in patients with autoimmune thyroiditis: evidence of Hashimoto's encephalitis?

Abstract: These findings of impaired brain perfusion in patients with autoimmune thyroiditis further strengthen the hypothesis of a possible cerebral involvement in autoimmune thyroiditis in individual cases. The presence of cerebral hypoperfusion suggests a cerebral vasculitis as the most likely pathogenetic model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 40 publications
(53 reference statements)
2
38
2
4
Order By: Relevance
“…Impaired brain perfusion in patients with known autoimmune thyroiditis has been demonstrated and supports a hypothesis of cerebral involvement in autoimmune thyroiditis [7,8,9]. However, a recent study showed that a 6-month levothyroxine treatment reduces systemic inflammation in patients with Hashimoto's thyroiditis.…”
Section: Discussionmentioning
confidence: 92%
“…Impaired brain perfusion in patients with known autoimmune thyroiditis has been demonstrated and supports a hypothesis of cerebral involvement in autoimmune thyroiditis [7,8,9]. However, a recent study showed that a 6-month levothyroxine treatment reduces systemic inflammation in patients with Hashimoto's thyroiditis.…”
Section: Discussionmentioning
confidence: 92%
“…One SPECT study concluded that the symptoms of HE are produced by the vasculitic disruption of the cerebral microvasculature [31]. Interestingly, two different groups of researchers performed SPECT scans in 60 euthyroid, neurologically intact patients with HT [64,91]. They found a higher than expected prevalence of cerebral hypoperfusion.…”
Section: Pathogenetic Hypothesesmentioning
confidence: 94%
“…Hadjivassiliou (29,30), thrombotic thrombocytopenic purpura (31) and ChurgStrauss syndrome (32) (2,33,34). Furthermore, SPECT studies have reported abnormal cerebral perfusion in celiac disease (35) and Hashimoto's thyroiditis with normal thyroid function (36 …”
Section: Selim and Drachman Reported That Two Of Six Patients With Anmentioning
confidence: 99%